1996
DOI: 10.1111/j.1365-2133.1996.tb01495.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous manifestations of systemic lupus erythematosus

Abstract: We have assessed the cutaneous signs in 73 patients with systemic lupus erythematosus (SLE), seen during a 5-year period in an English hospital. Most previous information about the cutaneous manifestations of SLE has been obtained from studies performed in the U.S.A. We classified lesions as specific cutaneous and mucosal LE (acute, subacute and chronic) or non-specific LE-related, e.g. photosensitivity, urticaria, erythema, Raynaud's phenomenon or vasculitis. Acute cutaneous LE lesions included a butterfly ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(73 citation statements)
references
References 32 publications
3
66
0
4
Order By: Relevance
“…We used the matched case-control data set to assess the construct validity of our study design. We tested for associations with a panel of factors documented in prior studies to be associated with SLE, including herpes zoster [6,7,34,35], urticaria [6,9], allergy to sulfonamides [10][11][12], and miscarriage [5]. Our analyses demonstrated associations that were consistent with prior studies and showed strong concordance with respect to effect size.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We used the matched case-control data set to assess the construct validity of our study design. We tested for associations with a panel of factors documented in prior studies to be associated with SLE, including herpes zoster [6,7,34,35], urticaria [6,9], allergy to sulfonamides [10][11][12], and miscarriage [5]. Our analyses demonstrated associations that were consistent with prior studies and showed strong concordance with respect to effect size.…”
Section: Discussionsupporting
confidence: 74%
“…Participants completed an online questionnaire about demographic factors, medications, comorbidities, common exposures, and a panel of factors consistently associated with SLE (miscarriage [5], shingles [6][7][8], hives [6,9], and allergy to sulfonamides [10][11][12][13]). We used standardized questions derived from previous studies [2,14].…”
Section: The Questionnairementioning
confidence: 99%
“…[7] Yell JA et al 31.5%. [8] In our study, the frequency of malar rash was 55.26%, while in study by Kole et al 80%. [2] , Parveen et al 70%.…”
Section: Discussionmentioning
confidence: 46%
“…[7] Yell JA et al 51%. [8] , Gronhagen CM et al 60%. [9] In our study the frequency of photosensitivity was 55.26%, while in study by Kole et al 50%.…”
Section: Discussionmentioning
confidence: 99%
“…O acometimento cutâneo é uma das manifestações mais comuns do lúpus eritematoso sistêmico (LES) que auxilia no diagnóstico e, muitas vezes, é a apresentação inicial da doença (Yell et al, 1996). Algumas dessas manifestações fazem parte dos 11 critérios diagnósticos estabelecidos pelo American College of Rheumatology (Anexo B) (Tan et al, 1982;Hochberg, 1997).…”
Section: Introductionunclassified